Digitalisasi Pelabuhan dalam Perspektif Administrasi Publik Studi Kasus Penerbitan Surat Persetujuan Berlayar dengan Sistem Inaportnet - Shinta Mardiana Dewi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The digital transformation of port services through the implementation of Inaportnet aims to enhance efficiency, transparency, and accuracy in maritime administration, particularly in the issuance of Surat Persetujuan Berlayar (SPB). However, its implementation faces various challenges, primarily in stakeholder coordination, involving Syahbandar (Harbormaster), Customs, Immigration, Port Health Quarantine (KKP), port operators, and shipping agents. This study analyzes key challenges in Inaportnet implementation, including regulatory misalignment between institutions, lack of system interoperability, inadequate digital infrastructure in several ports, and low digital literacy among users. Using a qualitative descriptive method with a literature review approach, this research examines various regulations, industry reports, and previous studies to identify obstacles and optimal strategies for Inaportnet adoption. The findings reveal that fragmented regulations across institutions lead to procedural inconsistencies, causing delays in SPB issuance. Additionally, limited interoperability between Inaportnet and other institutional systems, such as CEISA (Customs) and SIMKIM (Immigration), hampers document verification. Other barriers include digital infrastructure disparities, where 65% of feeder ports in Indonesia still experience limited internet access, and low digital literacy among system users, leading to data entry errors and administrative delays. To address these challenges, this study recommends harmonizing regulations, enhancing system interoperability, investing in digital infrastructure, and providing continuous technical training for stakeholders. With these strategies, Inaportnet is expected to function optimally, support port service digitalization, and enhance the competitiveness of Indonesia’s maritime sector in global trade.